2007
DOI: 10.1074/jbc.m707039200
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescens CHA0 Produces Enantio-pyochelin, the Optical Antipode of the Pseudomonas aeruginosa Siderophore Pyochelin

Abstract: The siderophore pyochelin is made by a thiotemplate mechanism from salicylate and two molecules of cysteine. In Pseudomonas aeruginosa, the first cysteine residue is converted to its D-isoform during thiazoline ring formation whereas the second cysteine remains in its L-configuration, thus determining the stereochemistry of the two interconvertible pyochelin diastereoisomers as 4R,2؆R,4؆R (pyochelin I) and 4R,2؆S,4؆R (pyochelin II). Pseudomonas fluorescens CHA0 was found to make a different stereoisomeric mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 67 publications
4
126
0
Order By: Relevance
“…Deletion of the SCAB1471 gene in the DSCAB1401 mutant abrogated production of the metabolite, confirming that it is a product of the PBGC. LC-MS analyses on a homochiral stationary phase confirmed that S. scabies produces pyochelin and not ent-pyochelin, consistent with the presence of a pchG orthologue (SCAB1461) and the absence of a pchK orthologue in the PBGC, as well as the presence of a putative methyl transferase-like epimerization domain in the PchE orthologue SCAB1481 (Youard et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Deletion of the SCAB1471 gene in the DSCAB1401 mutant abrogated production of the metabolite, confirming that it is a product of the PBGC. LC-MS analyses on a homochiral stationary phase confirmed that S. scabies produces pyochelin and not ent-pyochelin, consistent with the presence of a pchG orthologue (SCAB1461) and the absence of a pchK orthologue in the PBGC, as well as the presence of a putative methyl transferase-like epimerization domain in the PchE orthologue SCAB1481 (Youard et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
“…S1, available with the online version of this paper). The recent report of the isolation of ent-pyochelin from P. fluorescens prompted us to analyse the stereochemistry of pyochelin produced by S. scabies (Youard et al, 2007). Culture supernatants of the DSCAB1401 mutant were compared by LC-MS on a homochiral stationary phase with synthetic standards of pyochelin and ent-pyochelin (Youard et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…1; Youard et al, 2007). Enantio-pyochelin was found to promote growth of P. fluorescens under iron limitation and to upregulate its own biosynthesis genes in a manner similar to that of pyochelin in P. aeruginosa (Youard et al, 2007). However, enantio-pyochelin does not promote growth of P. aeruginosa and pyochelin has no such activity in P. fluorescens (Youard et al, 2007).…”
Section: Introductionmentioning
confidence: 85%
“…1; Youard et al, 2007). Enantio-pyochelin was found to promote growth of P. fluorescens under iron limitation and to upregulate its own biosynthesis genes in a manner similar to that of pyochelin in P. aeruginosa (Youard et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation